Gravitational Lensing: Strong, Weak and Micro Saas-Fee Advanced Course 33 - Schneider, Peter; Kochanek, Christopher; Wambsganss, Joachim; Meylan, Georges; Jetzer, Philippe; North, Pierre; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
The theory, observations, and applications of gravitational lensing constitute one of the most rapidly growing branches of astrophysics. The gravitational deflection of light generated by mass concentrations along a light path produces magnification, multiplicity, and distortion of images and delays photon propagation from one line of sight relative to another. The huge amount of scientific work on gravitational lensing produced over the last decade has clearly revealed its already substantial and wide impact and its potential for future astrophysical applications. The up-to-date contributions in this book are based on the lecture notes of the 33rd Saas–Fee Advanced Course of the Swiss Society of Astronomy and Astrophysics, entitled Gravitational Lensing: Strong, Weak, and Micro. The book comprises four complementary parts, written by leading experts in the field, constituting a genuine textbook about gravitational lensing: • Peter Schneider – Part 1: Introduction to Gravitational Lensing and Cosmology • Christopher Kochanek – Part 2: Strong Gravitational Lensing • Peter Schneider – Part 3: Weak Gravitational Lensing • Joachim Wambsganss – Part 4: Gravitational Microlensing Students and researchers alike will benefit from this comprehensive presentation of the astrophysical and astronomical aspects of gravitational lensing.
to Gravitational Lensing and Cosmology -- Strong Gravitational Lensing -- Weak Gravitational Lensing -- Gravitational Microlensing.
Keywords: Astrophysics; Astronomy; Cosmology; Gravitation; Observations, Astronomical; Astronomy—Observations.; Astrophysics and Astroparticles; Astronomy, Astrophysics and Cosmology; Cosmology; Classical and Quantum Gravitation, Relativity Theory; Astronomy, Observations and Techniques